2013
DOI: 10.5860/crl-292
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Experiences of African Librarians in American Academic Libraries

Abstract: A national research study was undertaken to identify and clarify issues related to the employment in academic settings of African librarians who have relocated to the United States. It examined, by means of a survey, employment issues concerned with education, credentialing, language skills and cultural bias from the perspective of those librarians and concluded with a recommendation regarding the manner in which their skills might be utilized for the benefit of their homelands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Because 20% or more of the cells in the contingency tables had expected counts of less than five, Fisher's exact tests were run rather than chi-square tests (Kim, 2017). When the test involved more than two-row by two-column contingency tables, the Freeman-Halton Extension of the Fisher's exact test was employed (Ibraheem & Devine, 2013). Moreover, this study examined Chinese Canadian librarians' experiences of microaggressions.…”
Section: Methodsmentioning
confidence: 99%
“…Because 20% or more of the cells in the contingency tables had expected counts of less than five, Fisher's exact tests were run rather than chi-square tests (Kim, 2017). When the test involved more than two-row by two-column contingency tables, the Freeman-Halton Extension of the Fisher's exact test was employed (Ibraheem & Devine, 2013). Moreover, this study examined Chinese Canadian librarians' experiences of microaggressions.…”
Section: Methodsmentioning
confidence: 99%
“…To explore the factors that might be associated with librarians' experience in each form of microaggression, Fisher's exact tests were conducted rather than chi-square tests because the expected counts were less than five in 20% or more of the cells in the contingency tables (Kim, 2017). The Freeman-Halton Extension of Fisher's exact test was employed for more than two rows by two-column contingency tables (Ibraheem & Devine, 2013). STATA 13 was used to perform all data analyses.…”
Section: Researchers Examined If Librarians' Microaggression Composit...mentioning
confidence: 99%
“…In Dalton et al (2018), the Black female law librarian's competency and authority as a supervisor were questioned; a White patron, in a separate event, showed surprise knowing that she had attended law school. A survey of the experiences of African librarians in American academic libraries revealed that more than 40% of the respondents had encountered workplace discrimination (Ibraheem & Devine, 2013). The qualifications of Black librarians for a job were often questioned, as indicated by Curry (1994):…”
Section: Microaggression #7: a Colleague Showed Surprise At My Profes...mentioning
confidence: 99%